Risk-based structural evaluation methods : best practices and development of standards - Ghosn, Michel; Fiorillo, Graziano; Liu, Ming; Ellingwood, Bruce R. (American Society of Civil Engineers, 2019)
Prepared by Technical Council on Life-Cycle Performance, Safety, Reliability, and Risk of Structural Systems of the Structural Engineering Institute of the American Society of Civil EngineersRisk-Based Structural Evaluation Methods: Best Practices and Development of Standards provides a comprehensive summary of the findings from a survey of attitudes of researchers, structural engineers, and government agencies to risk-informed structural engineering practices and a follow-up workshop. Risk analysis principles are well established from a theoretical point of view; however, a number of barriers have hampered a wide-scale implementation of risk-based methods in decision-making processes. This book examines the progress made on the application of risk-based structural evaluation methods (RBsEM) and provides recommendations to help enhance their implementation in engineering practice. The issues addressed includeRisk evaluation for new and existing structural systems, Hazard assessment and statistical projection of expected extreme natural and human-made events, Probabilistic analysis of structural systems, Assessment of physical damage to structures and infrastructure systems and evaluation of consequences, Estimation of associated direct and indirect losses and risk quantification, Risk communication to different stakeholders including the general public, Establishment of optimum risk acceptance criteria that take into consideration public attitudes toward risk, andPrioritization of risk mitigation strategies. This report will be a valuable resource for engineers, owners, regulators, and policy makers working toward implementation of RBsEM as the basis for managing our structure and infrastructure systems
Keywords: Structural failures -- Risk assessment.; Construction industry -- Risk management.; Buildings -- Standards.; elektronické knihy; electronic books